The role of EphA2 in ADAM17- and ionizing radiation-enhanced lung cancer cell migration - Waller, Verena; Tschanz, Fabienne; Winkler, Rona; Pruschy, Martin (Frontiers in Oncology, 2023)
Purpose Ionizing radiation (IR) enhances the migratory capacity of cancer cells. Here we investigate in non-small-cell-lung-cancer (NSCLC) cells a novel link between IR-enhanced ADAM17 activity and the non-canonical pathway of EphA2 in the cellular stress response to irradiation. Methods Cancer cell migration in dependence of IR, EphA2, and paracrine signaling mediated by ADAM17 was determined using transwell migration assays. Changes of EphA2 pS897 and mRNA expression levels upon different ADAM17-directed treatment strategies, including the small molecular inhibitor TMI-005, the monoclonal antibody MEDI3622, and shRNAs, were mechanistically investigated. ADAM17-mediated release and cleavage of the EphA2 ligand ephrin-A1 was measured using ELISA and an acellular cleavage assay. Results Irradiation with 5 Gy enhanced tumor cell migration of NSCLC NCI-H358 cells in dependence of EphA2. At the same time, IR increased growth factor-induced EphA2 S897 phosphorylation via auto- and paracrine signaling. Genetic and pharmaceutical downregulation of ADAM17 activity abrogated growth factor (e.g. amphiregulin) release, which reduced MAPK pathway-mediated EphA2 S897 phosphorylation in an auto- and paracrine way (non-canonical EphA2-pathway) in NCI-H358 and A549 cells. These signaling processes were associated with reduced cell migration towards conditioned media derived from ADAM17-deficient cells. Interestingly, ADAM17 inhibition with the small molecular inhibitor TMI-005 led to the internalization and proteasomal degradation of EphA2, which was rescued by amphiregulin or MG-132 treatment. In addition, ADAM17 inhibition also abrogated ephrin-A1 cleavage and thereby interfered with the canonical EphA2-pathway. Conclusion We identified ADAM17 and the receptor tyrosine kinase EphA2 as two important drivers for (IR-) induced NSCLC cell migration and described a unique interrelation between ADAM17 and EphA2. We demonstrated that ADAM17 influences both, EphA2 (pS897) and its GPI-anchored ligand ephrin-A1. Using different cellular and molecular readouts, we generated a comprehensive picture of how ADAM17 and IR influence the EphA2 canonical and non-canonical pathway in NSCLC cells.